PENERAPAN MODEL PEMBELAJARAN MASTERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAMDI KELAS VIII SMP MUHAMMADIYAH 6 MAKASSAR - Arif Ilham, Muh; Andi Bunyamin; Bambang Sampurno; Mustamin; Abdul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This thesis discusses "The Application of the Mastery Learning Model to Improve Student Learning Outcomes in Islamic Religious Education Subjects in Grade VIII of Muhammadiyah 6 Makassar Junior High School." The purpose of this study is to describe student learning outcomes in Islamic Religious Education Subjects in Grade VIII of Muhammadiyah 6 Makassar Junior High School. This study is a Classroom Action Research (CAR) consisting of two cycles, where each cycle consists of two meetings. The subjects in this study were 30 grade VIII students at Muhammadiyah 6 Makassar Junior High School. Data collection techniques in this study were observation, interviews, tests, and documentation. The data analysis techniques used in this study were formulas for calculating percentages and average values ​​(mean) for both the analysis of student activity sheet data and the completeness of student learning outcomes. After implementing Mastery Learning using two cycles, namely Cycle I and Cycle II, it can be seen that the learning outcomes of eighth-grade students in Islamic Religious Education have increased from the pre-cycle to Cycle II, which is in accordance with the results of tests conducted by researchers on students during the learning process in class. Where in the pre-cycle, the average score of students was 66.2 (sufficient) with a completion percentage of 33.33%. Then in Cycle I, the average score was 77.4 (good) with a completion percentage of 66.66%. In Cycle II, the average score was 88.5 (very good) with a completion percentage of 83.33%.